2005
DOI: 10.1126/science.1114037
|View full text |Cite
|
Sign up to set email alerts
|

Independent Codes for Spatial and Episodic Memory in Hippocampal Neuronal Ensembles

Abstract: Hippocampal neurons were recorded under conditions in which the recording chamber was varied but its location remained unchanged versus conditions in which an identical chamber was encountered in different places. Two forms of neuronal pattern separation occurred. In the variable cue-constant place condition, the firing rates of active cells varied, often over more than an order of magnitude, whereas the location of firing remained constant. In the variable place-constant cue condition, both location and rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

59
865
8
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 781 publications
(964 citation statements)
references
References 28 publications
59
865
8
1
Order By: Relevance
“…Upon entry into an environment, the balance of incoming sensory and stored information causes the hippocampal network to settle upon either the previously stored representation or a newly created representation. As revealed in place-cell recordings, in young rats a relatively modest change in environment or in task demands is sufficient to induce the switch from recalling a stored representation of the familiar environment to creating a new representation for the changed environment [83,84]. By contrast in aged rats, CA3 place-cell recordings indicate a propensity to recall stored representations rather than create new ones [82].…”
Section: A Model Of Information Processing In the Aged Hippocampusmentioning
confidence: 92%
See 1 more Smart Citation
“…Upon entry into an environment, the balance of incoming sensory and stored information causes the hippocampal network to settle upon either the previously stored representation or a newly created representation. As revealed in place-cell recordings, in young rats a relatively modest change in environment or in task demands is sufficient to induce the switch from recalling a stored representation of the familiar environment to creating a new representation for the changed environment [83,84]. By contrast in aged rats, CA3 place-cell recordings indicate a propensity to recall stored representations rather than create new ones [82].…”
Section: A Model Of Information Processing In the Aged Hippocampusmentioning
confidence: 92%
“…Of particular importance here, numerous studies have shown that CA3 and CA1 place cells of aged rats fail to encode new spatial or task information rapidly [78][79][80][81][82]. After young rats have explored one environment until it becomes highly familiar, introduction into a novel environment typically results in the creation of a new spatial representation, reflected in spatial firing patterns of hippocampal neurons that are drastically different from those associated with the familiar environment [83,84]. By contrast, in aged rats, place cells often retain the spatial firing patterns observed in the familiar environment when the animal is moved to the novel environment (Figure 2).…”
Section: Information Processing By Hippocampal Place Cells Of Aged Anmentioning
confidence: 99%
“…This suggestion, in its strictest form, was challenged by human clinical studies showing that patients with hippocampal damage had both spatial and nonspatial impairments (Squire et al, 2004) as well as observations in animals suggesting that some hippocampal cells express nonspatial information (Ranck, 1973;Young et al, 1994;Hampson et al, 1993;Wood et al, 1999;Ferbinteanu and Shapiro, 2003). However, it is now commonly believed that, in many or most hippocampal cells, this information is expressed on top of the spatial signal rather than instead of it (Leutgeb et al, 2005), and position is generally acknowledged as a major component of the signal carried by hippocampal neurons . This manifestation of a spatial code in hippocampal neurons has enabled researchers to take up Hebb's challenge and relate the discharge patterns of neuronal ensembles to a specific behavior, namely the ability to represent and recall the spatial environment and to use the neural representations to locate targets within that environment.…”
Section: Introductionmentioning
confidence: 97%
“…Converging evidence has suggested that hippocampal neurons respond also to nonspatial features of the environment, such as odors (Eichenbaum et al 1987;Wood et al 1999;Igarashi et al 2014), tactile inputs (Young et al 1994), and timing (Hampson et al 1993). The same cells that respond to nonspatial stimuli fire like place cells when animals move around in space, suggesting that place cells express the location of the animal in combination with information about events that take place or took place there (Leutgeb et al 2005b;Moser et al 2008). The representation of space does not exclude a central role of the hippocampus in declarative memory, as space is a central element of all episodic and many semantic memories (Buzsáki and Moser 2013).…”
Section: Place Cells Synaptic Plasticity and Memorymentioning
confidence: 99%
“…The remapping experiments showed that place cells participate in multiple spatial maps. Different maps could be recruited not only in different environments, but also when animals are tested under different conditions in the same location (Markus et al 1995;Leutgeb et al 2005b). Maps for different conditions or places were often completely uncorrelated (global remapping) (Leutgeb et al 2004;Fyhn et al 2007), as if a pattern-separation process takes place when information enters the hippocampus from the surrounding cortex (Marr 1971;McNaughton and Morris 1987;Leutgeb et al 2004Leutgeb et al , 2007.…”
Section: Remapping and Memorymentioning
confidence: 99%